2018
DOI: 10.2147/dddt.s149307
|View full text |Cite
|
Sign up to set email alerts
|

Vicenin-2 inhibits Wnt/β-catenin signaling and induces apoptosis in HT-29 human colon cancer cell line

Abstract: BackgroundColorectal cancer (CRC) is among highest prevailing cancers in the whole world, especially in western countries. For a diverse of reasons, patients prefer naturally occurring dietary substances over synthetic agents to prevent cancer. Vicenin-2 is largely available in a medicinal plant Ocimum sanctum and is an apigenin form, 6,8-di-C-glucoside, which has been reported to have a range of pharmacological values which includes antioxidant, hepatoprotective, anti-inflammatory and anti-cancer. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Here, we showed that DB treatment not only suppressed colon tumorigenesis, but also CSC phenotypes. DB-medicated CSC-inhibitory effects were associated with the decreased expression of the IGF downstream oncogenic marker, mTOR/STAT3, as well as the stemness marker, β-catenin, both of which have been reported to contribute to treatment failure and the recurrence of colon cancer [ 23 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that DB treatment not only suppressed colon tumorigenesis, but also CSC phenotypes. DB-medicated CSC-inhibitory effects were associated with the decreased expression of the IGF downstream oncogenic marker, mTOR/STAT3, as well as the stemness marker, β-catenin, both of which have been reported to contribute to treatment failure and the recurrence of colon cancer [ 23 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, apoptosis-related proteins showed significant roles in regulating chemoresistance. Yang et al [29] reported that Vicenin-2 induces apoptosis in colon cancer by suppressing Bcl-2 and enhancing the expression of Bax and caspase-3 through Wnt/β-catenin signaling. Li et al [30] demonstrated that silencing aquaporin-5 could enhance the sensitivity of CRC cells to 5-FU by inducing apoptosis through the Wnt/β-catenin signaling pathway.…”
Section: Wnt/β-catenin Signaling and Cell Apoptosis In Drug Resistancmentioning
confidence: 99%
“…ViceninII, or 6,8-di-C-glucoside of apigenin, a nontoxic flavonoid that was originally identified from Vitex lucens wood and that is present in many plant sources in Southern Asia, such as Dendrobium officinale , Urtica circularis , Lychnophora and other species [40,41,42], is an effective anti-inflammatory [43,44,45,46], antiglycation [47], anti-spasmodic [48], antiseptic [49], antithrombotic, and antiplatelet agent [50]. ViceninII exhibits significant anticancer activities that inhibit the growth of prostate cancer (PC-3, DU-145 and LNCaP cells) in-vitro and in-vivo [51,52] and induce apoptosis in hT-29 human colon cancer cells [53]. In addition, many critical literatures has been reported that ViceninII has shown anti-inflammatory effect through the inhibition of TGF-β-induced protein signaling pathway as well as induced apoptosis of lung cancer H23 cell via PI3K/Akt/mTOR signaling [54,55].…”
Section: Introductionmentioning
confidence: 99%